2022
DOI: 10.1007/s10803-021-05413-x
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Adjustments for Autistic Employees: What is ‘Reasonable’?

Abstract: Autistic adults are inadequately supported in the workplace. This study sought a definition of ‘reasonable’ and explored facilitators and barriers to employers making reasonable adjustments. 98 employers and employees across a UK city completed a survey; 15% identified as being autistic. Qualitative data were analysed using framework analysis. Reasonable adjustments were defined as having a positive impact on autistic employees’ wellbeing and work outputs without being detrimental to non-autistic employees or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…For example, we found that the negative sensory impacts of the school environment could be significantly mitigated by Covid-related measures, even though this was not their primary aim. Indeed, sensory hypersensitivity in the workplace is "a largely invisible and unknown disability" (de Vries, 2021, p. 284) that can create a barrier to well-being and self-efficacy without reasonable adjustments (Petty et al, 2022). Some adaptations, such as remote-working, although not available to all, meant that participants were more able to manage their own sensory environment, showing an instructive intersection between sensory well-being and agency in our study.…”
Section: Discussionmentioning
confidence: 70%
“…For example, we found that the negative sensory impacts of the school environment could be significantly mitigated by Covid-related measures, even though this was not their primary aim. Indeed, sensory hypersensitivity in the workplace is "a largely invisible and unknown disability" (de Vries, 2021, p. 284) that can create a barrier to well-being and self-efficacy without reasonable adjustments (Petty et al, 2022). Some adaptations, such as remote-working, although not available to all, meant that participants were more able to manage their own sensory environment, showing an instructive intersection between sensory well-being and agency in our study.…”
Section: Discussionmentioning
confidence: 70%
“…Providing people with ASD with social skills training delivered in a group format is associated with modest effects on social competence . Effective therapies are needed to help people with ASD succeed in postsecondary education and the work environment …”
Section: Discussionmentioning
confidence: 99%
“…Research is made difficult by the low number of autistic colleagues being truly represented in industry. A second important contextual consideration is the legal obligation that employers are under in the UK to ensure that employees are not disadvantaged at work by their autism diagnosis (the Autism Act, 2009; the Equality Act, 2010) by making appropriate working adjustments (Petty et al, 2022). Despite this context, the understanding of support that can be provided in the workplace was shown to be lower than the understanding of the difficulties faced or the positive contributions of autistic employees.…”
Section: Conclusion and Areas For Further Researchmentioning
confidence: 99%
“…The study variables were identified from a literature review: understanding of autism in the workplace and confidence in providing appropriate workplace support have been identified by autistic adults (López and Keenan, 2014), by representation from some employment sectors in the UK (Buckley et al, 2020) and by some workplaces internationally (Lindsay et al, 2021) as barriers to the employment of autistic adults. These quantitative questionnaire data formed part of a larger qualitative dataset that explored definitions of reasonable adjustments (Petty et al, 2022).…”
Section: Workplace Surveymentioning
confidence: 99%
See 1 more Smart Citation